Degradation and erosion mechanisms of bioresorbable porous acellular vascular grafts: an in vitro investigation. Issue 132 (12th July 2017) - Gade, Piyusha S.; Lee, Keewon; Pfaff, Blaise N.; Wang, Yadong; Robertson, Anne M.
Abstract : A fundamental mechanism of in situ tissue regeneration from biodegradable synthetic acellular vascular grafts is the effective interplay between graft degradation, erosion and the production of extracellular matrix. In order to understand this crucial process of graft erosion and degradation, we conducted an in vitro investigation of grafts ( n = 4 at days 1, 4, 7, 10 each) exposed to enzymatic degradation. Herein, we provide constitutive relationships for mass loss and mechanical properties based on much-needed experimental data. Furthermore, we formulate a mathematical model to provide a physics-based framework for understanding graft erosion. A novel finding is that despite their porous nature, grafts lost mass exponentially via surface erosion demonstrating a 20% reduction in outer diameter and no significant change in apparent density. A diffusion based, concentration gradient-driven mechanistic model of mass loss through surface erosion was introduced which can be extended to an in vivo setting through the use of two degradation parameters. Furthermore, notably, mechanical properties of degrading grafts did not scale with mass loss. Thus, we introduced a damage function scaling a neo-Hookean model to describe mechanical properties of the degrading graft; a refinement to existing mass-dependent growth and remodelling (G&R) models. This framework can be used to improve accuracy of well-established G&R theories in biomechanics; tools that predict evolving structure–function relationships of neotissues and guide graft design.